Peran Industri Tahu terhadap Pengembangan Ekonomi Masyarakat di Dukuh Kesambi Desa Pundenrejo - Hidayah, Nur; Naharin, Sri (Mafa Press, 2025)
This study aims to analyze the role of the Barokah Kesambi tofu industry in Dukuh Kesambi, Pundenrejo Village, Tayu District, Pati Regency, in fostering community economic development and the resulting social dynamics. Using a field research approach with participant observation, unstructured interviews, and documentation, the findings reveal that the tofu industry significantly contributes to local economic growth through job creation, skill development, and the strengthening of social solidarity. The industry fosters social integration, workers’ adaptation to economic changes, and the transmission of work values that reinforce community cohesion. However, social stratification remains evident due to unequal access to resources between owners and workers. Therefore, participatory empowerment programs, human resource development, and economic diversification are essential to reduce inequality and promote sustainable local development.